Planktonic archaeal phosphorus affinity and apportionment (PAPAA) - Travis B Meador; Niels J Schoffelen; Timothy G Ferdelman; Osmond Rebello; Alexander Khachikyan; Martin Könneke (PANGAEA, 2020)
Complete cell count, nutrient concentration, and radiotracer data for culture incubations and results presented in the manuscript "Carbon recycling efficiency and phosphate turnover by marine nitrifying archaea". This includes measurement of the following parameters for up to nine time points in cultures of N. maritimus strains NAOA6 and SCM1: For each culture incubation, the time points where C and P uptake rates were considered to be first-order are identified by a value of 1 in the column "Linear Y/N". Columns headed by "SD" provide the standard deviation of the value listed in the column to the immediate left.